The Millennial Generation's Interest in Cash Waqf Linked Sukuk (CWLS) on the Island of Java - Rosida, Rida; Oktaviani, Nola; Nurasyiah, Aas (Review of Islamic Economics and Finance, 2024)
Purpose – The purpose of this research is to conduct an empirical analysis to obtain theories and concepts, examine and delve into the influence of attitudes, subjective norms, waqf literacy, income levels, and trust in waqf institutions on the millennial Muslim community's interest in cash waqf linked Sukuk (CWLS).Methodology—The method used is a hypothesis testing procedure using a quantitative approach. The analysis tool utilized is Partial Least Square-Structural Equation Modeling (PLS-SEM) using SmartPLS.Findings —The research findings indicate that attitudes, subjective norms, waqf literacy, and trust in waqf institutions positively and significantly affect interest in waqf. However, the income level does not affect interest in waqf.Keywords: Cash Waqf Linked Sukuk (CWLS); interest in waqf; trust in waqf institution; waqf; waqif behavior.